2020
DOI: 10.51201/jusst12507
|View full text |Cite
|
Sign up to set email alerts
|

Job Marketable for Student with Disability: What We Should Know for Career Transition Programme

Abstract: People with disabilities face the greatest challenge of getting a job. This is because of thelow marketability skills of this group. Career transition programme (CTP) has been introduced to students with disabilities (SWDs) to prepare and train them for job market.Skills training in the field of employment is provided to SWDs in the implementation of CTP. However, it is still difficult for this group to get a job despite having good skills.A survey study was conducted to identify the marketability skills requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For example, students with strong and clear communication skills can indirectly develop a good working relationship with other students or future co-workers (Lindsay et al, 2019). Besides that, students who can manage themselves can avoid from feeling discomfort in a new working environment and thrive to achieve excellence in work (Zainal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, students with strong and clear communication skills can indirectly develop a good working relationship with other students or future co-workers (Lindsay et al, 2019). Besides that, students who can manage themselves can avoid from feeling discomfort in a new working environment and thrive to achieve excellence in work (Zainal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although SSEN is exposed and trained with various skills throughout CTP, it was found that SSEN working ability is low (Ratnam et al, 2018;Zainal et al, 2020) while having attitude and communication problem, hard to understanding instruction and difficult in adapting to working environment . Besides that, employers have less knowledge regarding SSEN (Azlan & Alias, 2016), unconfident of their working abilities and reluctant to accept them as a trainee (Abdullah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%